2003
DOI: 10.1001/archinte.163.9.1110
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Infarction in a Patient With Acute Pulmonary Embolism and Normal Coronary Arteries

Abstract: Figure 2. Heart scintigraphy with technetium Tc 99m pyrophosphate detected abnormal isotope uptake within the right ventricle and left ventricular inferior wall (omega sign), suggestive of acute myocardial damage. LAO indicates left anterior oblique plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
1
11
0
2
Order By: Relevance
“…[12][13][14] Moreover, autopsy and scintigraphic case series reported RV MIs in patients with major APE. 15,16 Therefore, larger RV dimension and higher Tei index found at follow-up in the APE group may result from damage-induced RV remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Moreover, autopsy and scintigraphic case series reported RV MIs in patients with major APE. 15,16 Therefore, larger RV dimension and higher Tei index found at follow-up in the APE group may result from damage-induced RV remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary embolism can cause right ventricular infarction. 183,184 Hypotension, hypertension and tachycardia could contribute with or without concomitant coronary artery disease. Troponin elevations are more likely to occur in patients with shock 185,186 and clinical variables 187,188 associated with poor outcome.…”
Section: Other Clinical Situations In Which Troponin Levels May Be Elmentioning
confidence: 99%
“…It has also been predicted that severe PE increases RV wall tension, causing both shear force injury to myocytes and compression of the right coronary artery (23,24). Although case reports have associated massive PE with frank RV infarction, and patients with RV dysfunction do liberate contractile proteins such as troponins into the blood, no study has shown evidence to support RV tissue necrosis as the primary cause of RV contractile dysfunction observed after PE (25,26). Indeed, postmortem histological analyses of RV muscle from humans with fatal PE demonstrated the accumulation of neutrophils and monocyte/macrophages in the RV but without histological evidence of infarction (27,28).…”
Section: Inhibition Of Cinc-1 Decreases Right Ventricular Damage Causmentioning
confidence: 99%